FRAGMENTATION AND CONFLICT AMONG ISLAMIC POLITICAL PARTIES IN INDONESIA DURING REFORMASI ERA (1998-2009): Anatomy, Factors and Implications - Sri Yunanto; Ahmad Fauzi Abdul Hamid (JOURNAL OF INDONESIAN ISLAM, 2013)
Since independence of the Republic of Indonesia, Muslims, as the majority population, have established diverse Islamic political parties. The nature of such parties has changed from the days of the Old Order to the New Order and Reformasi eras. Despite similar anatomies between Islamic parties of the Old Order and those of Reformasi, Islamic political parties profess different ideological missions. While the beginning of Old Order saw the confederation of Islamic political parties, Masyumi, seeking to promote the establishment of an Islamic State, none of the Islamic political parties which mushroomed during Reformasi era expressly struggled for the establishment of an Islamic state. However, the Islamic political parties had to weather similar problems of internal conflict and fragmentation. Different ideological strands, policy stances and leadership styles are believed to be amongst the pivotal root causes of their domestic troubles. With their popular votes and parliamentary seats significantly reduced, they prove to be no competition to the nationalist political parties.